Evaluation of short-term gastrointestinal motion and its impact on dosimetric parameters in stereotactic body radiation therapy for pancreatic cancer. (March 2023) - Uchinami, Yusuke; Kanehira, Takahiro; Fujita, Yoshihiro; Miyamoto, Naoki; Yokokawa, Kohei; Koizumi, Fuki; Shido, Motoyasu; Takahashi, Shuhei; Otsuka, Manami; Yasuda, Koichi; Taguchi, Hiroshi; Nakazato, Keiji; et al.
Highlights: The short-term GI-tract motion was assessed in eleven pancreatic cancer patients. Dose uncertainties were also evaluated with SBRT of 40 Gy in 5 fractions. The necessary margin was at least 8 mm to compensate for the organ motion. The short-term motion could lead to unexpectedly high doses in parts of the GI-tract. The results of this study have important implications for intra-fractional motion. Abstract: Background: The aim of this study is to quantify the short-term motion of the gastrointestinal tract (GI-tract) and its impact on dosimetric parameters in stereotactic body radiation therapy (SBRT) for pancreatic cancer. Methods: The analyzed patients were eleven pancreatic cancer patients treated with SBRT or proton beam therapy. To ensure a fair analysis, the simulation SBRT plan was generated on the planning CT in all patients with the dose prescription of 40 Gy in 5 fractions. The GI-tract motion (stomach, duodenum, small and large intestine) was evaluated using three CT images scanned at spontaneous expiration. After fiducial-based rigid image registration, the contours in each CT image were generated and transferred to the planning CT, then the organ motion was evaluated. Planning at risk volumes (PRV) of each GI-tract were generated by adding 5 mm margins, and the volume receiving at least 33 Gy (V33 ) < 0.5 cm 3 was evaluated as the dose constraint. Results: The median interval between the first and last CT scans was 736 s (interquartile range, IQR:624–986). To compensate for the GI-tract motion based on the planning CT, the necessary median margin was 8.0 mm (IQR: 8.0–10.0) for the duodenum and 14.0 mm (12.0–16.0) for the small intestine. Compared to the planned V33 with the worst case, the median V33 in the PRV of the duodenum significantly increased from 0.20 cm 3 (IQR: 0.02–0.26) to 0.33 cm 3 (0.10–0.59) at Wilcoxon signed-rank test (p = 0.031). Conclusion: The short-term motions of the GI-tract lead to high dose differences.